Mental and physical health, impulse control, and intimate partner violence within a veteran sample - Grigorian, Hannah L.; Hailes, Helen P.; Palm Reed, Kathleen M.; Reilly, Erin D. (Frontiers in Psychology, 2025)
IntroductionPsychiatric (e.g., PTSD, alcohol use disorder) and physical issues (e.g., chronic pain, sleep problems) are robustly associated with the use of intimate partner violence (IPV). These chronic conditions can amplify the likelihood of IPV use by increasing perceived threat, poor relationship quality, and negative affect while simultaneously decreasing the ability to inhibit violent behavior. However, the research in this area has largely been examined in limited samples or by examining a single chronic condition above diagnostic cut-offs or specific dual diagnosis (e.g., PTSD and alcohol use disorder). Further, potential mechanisms of action such as impulse control difficulties are rarely included in analyses.MethodsThe current study aimed to extend prior research by examining mental health issues, physical health conditions, and impulse control difficulties in a cross-sectional survey design with a final community-based sample of 251 Veterans (188 male).ResultsAt the bivariate level, overall, psychological, and physical IPV use were respectively and positively associated (p < 0.05) with PTSD symptoms, alcohol use, chronic pain, sleep problems and impulse control difficulties; sexual IPV use was positively associated with all of these risk factors as well, except chronic pain. Within multiple regression analyses, impulse control difficulties were positively associated with overall IPV use (β = 0.28, t = 2.39, p = 0.02), psychological IPV (β = 0.44, t = 4.06, p < 0.001), physical IPV (β = 0.40, t = 3.39, p < 0.001), and sexual IPV (β = 0.40, t = 3.33, p = 0.001), even when controlling common demographic predictors (e.g., age, gender, income, social desirability) and in the context of other diagnostic risk factors (e.g., mental and physical health symptoms).DiscussionFindings suggest that difficulty inhibiting behavior when experiencing negative affect may be an important factor for IPV use in the context of multiple common psychiatric and physical issues. This potential area for intervention should be thoroughly examined in longitudinal and experimental designs.